Understanding self‐ascription. (17th May 2019) - Jackson, Frank; Stoljar, Daniel
Abstract: David Lewis argues that believing something is self‐ascribing a property rather than holding true a proposition. But what is self‐ascription? Is it some new mysterious primitive? Is Lewis saying that every belief you have is about you? Several recent authors have suggested that, in the light of these questions, Lewis's theory should be rejected, despite its enormous influence. But this neglects the fact that Lewis makes two relevant proposals about belief: one about belief de se, another about belief de re . It is the second that prompts these questions but the first that is central to his theory.